Alterations of muscular strength and left and right limb balance in weightlifters after an 8-week balance training program - Kang, S. H.; Kim, C. W.; Kim, Y. I.; Kim, K. B.; Lee, S. S.; Shin, K. O. (Journal of Physical Therapy Science, 2013)
[Purpose] Balance is generally defined as the ability to maintain the body`s center of gravity within its base of support and may be categorized by either static or dynamic balance. The purpose of the present study was to evaluate the effect of 8 weeks of balance training on strength, and the functional balance ability of elite weightlifters. [Subjects] Thirty-two elite weightlifters were recruited for the present study. They were divided into exercise groups (8 high school students, 8 middle school students) and control groups (8 high school students, 8 middle school students). [Methods] Body compositions were measured by the electrical impedance method, and a Helmas system was used to measure basic physical capacities. The muscular function test was conducted using a Cybex 770. [Results] There were no significant changes in body composition after the training. In contrast, significant changes were found in the number of push-ups, one-leg standing time with eyes closed, and upper body back extension. Interestingly, only the left arm external rotation value after the exercise training program showed a statistically significant difference from the baseline value. [Conclusion] The peak torque values of shoulder internal rotation and knee extension were significantly changed compared to the baseline values, which mean subjects showed balance of their muscular power. Therefore, the results of the present study suggest that an 8-week balance-training program would positively affect elite weightlifters` balance ability and flexibility. We think that well-balanced muscular functionality may enhance athletes` sport performance.